THE USE OF GUESSING FROM CONTEXT TECHNIQUE TO INCREASE STUDENTSâ€™ VOCABULARY - Fitaloka, Yuniarti; Marbun, Rismaya; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research focuses on the use of Guessing from Context Technique to increase studentsâ€™ vocabulary. The aim of conducting this research is to investigate whether or not the use of guessing from context technique is effective to increase studentâ€™s vocabulary on tenth grade students of SMAN 1 Ambawang, Kubu Raya in academic year 2014/2015. The researcher conducted a pre-experimental study with measurement as the technique of collecting data and written test as tool of collecting data. The sample of this study was 28 students. The research finding show that the mean score of pre-test is 46.85; which is categorized as â€œPoorâ€. Furthermore, the mean score of post-test was 68.07; which is categorized as â€œAverage to Goodâ€. Based on the data analysis, it was found that the effect size of this research is 4.93. It can be concluded that there is a significant effect in the use of guessing from context technique in the Senior High School students. Â Key words: Guessing from Context, vocabulary, pre-experimental Abstrak: Penelitian ini fokus pada penggunaan Guessing from Context teknik untuk meningkatkan kosa kata siswa dalam pembelajaran. Tujuan melakukan penelitian ini adalah untuk mengetahui apakah guessing from context efektif atau tidak untuk meningkatkan kosa kata siswa kelas sepuluh SMAN 1 Ambawang, Kubu raya pada tahun ajaran 2014/2015. Penelitian dilakukan dalam bentuk penelitian pre-experimental menggunakan tehnik pengukuran sebagai tehnik pengolahan data serta tes menulis sebagai cara mengumpulkan data. Penelitian ini melibatkan sampel sebanyak 28 siswa. Hasil dari penelitian ini mendapatkan nilai rata rata pre-test nya adalah 46,85; termasuk kategori â€œrendahâ€. Kemudian, nilai rata-rata dari post-test adalah 68,07; termasuk kategori â€œrata-rata ke baikâ€. Berdasarkan analisis data, ditemukan bahwa ukuran efektifitas dari penelitian ini adalah 4,93. Ini dapat disimpulkan bahwa ada efek yang yang signifikan dari penggunaan guessing from context untuk meningkatkan kosa kata pada siswa Sekolah Menengah Atas. Â Kata kunci: guessing from context, kosa kata, pre-experimental